DIY electronic stethoscope with cloud storage - Ong, Clement Xin Quan (Nanyang Technological University, 2022)
The objective of this project is to develop an electronic stethoscope circuit using an electret condenser microphone. The input from the microphone is passed through the electronic circuit to amplify the signals. Processed signals from the electronic stethoscope will output to a pair of earbuds. Two variations of electronic stethoscopes with different preamplifiers are created to compare the quality and volume. The two variations of preamplifiers are created using general purpose op-amp TL072 and 2N3904 transistor.